Hospital and Health Information Systems – Current Perspectives - Lovis, C.; Ball, M.; Boyer, C.; Elkin, P. L.; Ishikawa, K.; Jaffe, C.; March, A.; Marin, H.; Mykkänen, J.; Rienhoff, O.; Silva, J.; Sittig, D. F.; Talmon, J. (Yearbook of Medical Informatics, 2011)
To celebrate over 30 years of health information systems’ (HIS) evolution by bringing together pioneers in the field, members of the next generation of leaders, and government officials from several developing nations in Africa to discuss the past, present, and future of HISs.Participants gathered in Le Franschhoek, South Africa for a 2 ½ day working conference consisting of scientific presentations followed by several concurrent breakout sessions. A small writing group prepared draft statements representing their positions on various topics of discussion which were circulated and revised by the entire group.Many new tools, techniques and technologies were described and discussed in great detail. Interestingly, all of the key themes identified in the first HIS meeting held over 30 years ago are still of vital importance today: Patient Centered design, Clinical User Support, Real-time Education, Human-computer Factors and Measuring Clinical User Performance, Meaningful use.As we continue to work to develop next-generation HISs, we must remember the lessons of the past as we strive to develop the solutions for tomorrow.
Keywords: Hospital information system; medical informatics; nursing informatics; public health informatics; computers